Progress of early warning indicators on infectious diseases - FU Meihua; TAO Fangfang; CHEN Jian (Shanghai yufang yixue, 2024)
In recent years， with frequent outbreaks of infectious diseases around the world， the global public health is faced with many threats and challenges. An infectious diseases early warning system is an important means for prevention and control of infectious diseases. As an important part of the early warning system， the warning indicators is crucial for understanding the occurrence and development trend of infectious diseases， detecting abnormal situations timely and effectively， and issuing early warning and initiating emergency response. Based on the occurrence and development process of infectious diseases， this paper summarizes the research status of early warning indicators on infectious diseases， in order to provide reference for the development and improvement of the infectious diseases early warning system.